IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS WEB PADA MATERI IKATAN KIMIA (JS (JURNAL SEKOLAH), 2023)
Abstract: Implementation of Web-Based Learning Media on Chemical Bonding Materials. This study aims to determine the learning outcomes using web-based learning media is greater than the KKM value on chemical bonding material. The One Sample t-test was used in this study to see certain values that were compared with the average (mean) values of the samples declared to be significantly different or not. The instrument in this study is an objective test in the form of multiple choice questions that have been validated and tested for feasibility. The data analysis technique to determine the results of the study was carried out by testing the normality of the data and then testing the hypothesis using IBM SPSS Statistics 22 for Windows. The results of the hypothesis test obtained that the value of sig (2-Tailed)